Thyroid carcinoma in woman. gynecologist view - Т. Ф. Татарчук; Л. В. Калугіна; А. О. Данилова (Publishing House TRILIST, 2019)
Over the past decade the incidence of thyroid cancer in Ukraine has increased 1.5 times, and the average age of diagnosis among women is 36 years. Thyroid cancer is the most common endocrine cancer, occurs in 5-10% of patients with thyroid nodules. Papillary carcinoma is 80% of all thyroid malignant neoplasms and is three times more common in women than in men. The peak incidence in women is observed in 40-49 years, while in men the peak is 60-69 years. In addition to established risk factors such as female sex, exposure to ionizing radiation, a history of benign thyroid disease, deficiency or excess of iodine in the diet, somatic mutations BRAFV600E, RET/PTC, NTRK, remain relevant studies of the role of estrogen imbalance and progesterone and progesterone expression of their receptors sensitive in the development of thyroid carcinogenesis. Recent studies devoted to improving the diagnosis of thyroid cancer, surgical intervention techniques, subsequent radioactive iodine therapy and duration of thyroid stimulating hormone suppression. Thanks to this patients with thyroid papillary carcinoma have favorable prognoses, because the 5-year survival rate is more than 98%. According to the American Thyroid Association a modern approach to the treatment of papillary thyroid cancer has several stages and depends on the recurrence risk in a patient. Thus, patients in accordance with the tumor size, the presence of local, distant metastases, BRAF V600E mutations, etc. are divided into three groups: low, medium and high risk of developing a relapse. At the first stage of treatment surgical intervention (thyroidectomy or lobectomy) is performed, followed by histopathological verification of the diagnosis, radioiodine diagnosis of the presence of metastases, evaluation of risk factors for recurrence, and the decision to conduct a course of radioiodine therapy during the second stage of treatment. The further management of these patients also depends on the risk group and includes the long-term suppressive treatment of thyroid stimulating hormone with levothyroxine.